ANALYSIS OF APPLICATION OF RECORDABLE INCIDENT RATE IN HEALTH AND SAFETY MANAGEMENT SYSTEMS AT PT SEMEN PADANG - Taufiq Ihsan; Bingesti Vegi Mayolan; Suci Mutiara Yardi; Tivany Edwin (Faculty of Public Health, Andalas University, 2019)
PT Semen Padang was the oldest cement industry in Indonesia located in Indarung, Padang City, West Sumatra. To protect the safety and health of workers, PT Semen Padang conducts an Occupational Health and Safety (OHS) Management System by controlling the Recordable Incident Rate (RIR) number. PT Semen Padang used Minister of Manpower Regulation No. 03 / Men / 1998 to calculate RIR numbers because itÂ has more than 500 workers. The number of RIRs obtained from 2013-2017 experienced fluctuations. The highest RIR rate was 2.50 in 2016Â and was above the target of PT Semen Padang, which amounted to 2.0. In suppressing the RIR figures, PT Semen Padang implemented an activity plan, in the form of inspection, socialization and informationÂ of OHS. Viewed from 2013-2017 the magnitude of the implementation of the activity plan had a significant effect on the decrease in the RIR rate in PT Semen Padang (p <0.05). The solution for RIR activity plan improvement can be in the form of increasing the frequency of inspections carried out in locations with high risk of accidents, socialization of OHS based on the type of dominant occupational accidents and proper placement of OHS information in the work area.